The Use of Interactive Multimedia in The Era of Society 5.0 in Elementary Schools in Improving Learning Outcomes of Natural and Social Sciences (IPAS) - Ayuningtyas, Mentari; Rokhmaniyah, Rokhmaniyah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
The era of Society 5.0 makes technology the centre of learning, through the use of interactive multimedia as an important tool for Natural and Social Sciences (IPAS) subjects in elementary schools. The purpose of this study is to examine the utilisation of interactive multimedia in improving student learning outcomes. This research uses descriptive qualitative method with interview, observation, and documentation techniques. The results of this study show that although multimedia facilities are available at school, teachers rarely use them and rely more on traditional methods such as lectures and memorisation. Effective strategies are needed to improve the quality of education as well as training for teachers to maximise the use of interactive multimedia in learning. The use of interactive multimedia is proven to improve students' motivation, enthusiasm and learning outcomes by making learning more interesting, concrete and interactive. This research emphasises the importance of technology integration in education to create a more effective and relevant learning process in this digital era.